KEMAMPUAN MENULIS TEKS DRAMA PADA SISWA KELAS VIII SMP NEGERI 25 BANDAR LAMPUNG - Dian Permanasari (LPPM STKIP PGRI Bandar Lampung, 2019)
This study contains the ability to write drama text in grade VIII students in the odd semester of SMP Negeri 25 Bandar Lampung. What is the level of ability of VIII grade students of SMP Negeri 25 Bandar Lampung in writing drama texts. This study aims to find out and describe the level of students' ability to write drama texts that are viewed in terms of several aspects, namely aspects of the plot, character and characterization, style of language, background, point of view and theme.The method used is descriptive qualitative by using percentages, namely by analyzing aspects, namely aspects of flow, character and characterization, style of language, background, perspective and theme. The ability of the drama text of SMP Negeri 25 Bandar Lampung in the aspects of the background and angle of understanding in the category is quite seen from the percentage of students who have an average value of 62.8% and the ability to write drama texts for SMP Negeri 25 Bandar Lampung in the theme aspects category is less seen from the percentage of students who have an average value of 60%.